Integrasi Pendidikan Nilai Dalam Pembelajaran Sejarah Sebagai Upaya Mempersiapkan Generasi Emas - Muhammad Fitri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Value education is a process of teaching or guiding students to realize the truth, goodness, and beauty through the process of considering the right values and habituation to act consistently. through the process of learning history. The method used is a literature review which consists of five stages including: (1) defining the scope of the topic to be reviewed, (2) identifying relevant sources, (3) reviewing the literature, (4) writing a review and (5) applying literature on the study to be carried out. This writing aims to describe the integration of value education in history learning as an effort to prepare the golden generation. The results of the literature review show that the integration of value education is important to instill in students through the history learning process. Based on the results of the literature review, it can be concluded that the integration of value education in Brata history learning plays an important role as an effort to prepare the golden generation.